Überpumpung als Manmade Hazard im Sousstal (Südmarokko).: Sozialgeographische Aspekte exzessiver Grundwasserausbeutung - Popp, Herbert (ERDKUNDE, 1983)
It was only in the1940s that the European colonization of the Souss valley took place. In those days especially French stock companies bought large areas, on which the ground water was exploited by means of motor pumps in order to irrigate citrus trees. Later, in the course of the decolonization of the European landed properties, a new class of investors from Moroccan towns came to the Souss valley and initiated the expansion of the area of citrus trees and of pump irrigation. Because of the severe exploitation of ground water the ground water level, in the lower Souss valley especially, sank by 40-50 metres. As a consequence of the water shortage, which meanwhile has become a hazard, considerable areas of citrus trees had to be abandoned. Depending on the availability of capital and on the readiness to take a risk the farm owners react in rather different ways to the hazard: 1) Large farms introduce new, water-saving technologies such as micro-sprinkler and trickle irrigation. 2) Medium-size and small farms on the former European land show a large variety of reactions, from expanding to abandoning their area of citrus trees. 3) Small farms on melk-land were largely deprived of their agricultural living. In the struggle for ground water the farms lacking capital fared worst. In view of the catastrophic situation of water supply from the aquifer the overall concept of the FAO for a further overpumping in the Souss valley has without doubt to be regarded as questionable.